Systematic Literature Review: Trends Computational Thinking and Mathematical Disposition in Mathematics Learning - Azizia, Ananda Jullailatul; Masrukan, Masrukan; Susilo, Bambang Eko (Universitas Islam Sultan Agung, 2024)
Abstract. This research aims to provide comprehensive information on the trend of computational thinking ability and mathematical disposition in mathematics learning. The method used was a Systematic Literature Review (SLR). Data was collected by reviewing articles on computational thinking skills and mathematical disposition published in 2019-2024. There were 15 articles, nine related to computational thinking ability and six related to mathematical disposition, obtained from Google Scholar and Scopus. The results of this study indicate that the methods and research designs that tend to be used for research on computational thinking ability and mathematical disposition tend to use quantitative research with quasi-experimental design, and PBL learning models are widely used. Research on thinking ability is predominantly carried out on elementary school students but for mathematical disposition at the junior and senior high school levels with geometry, algebra, and statistics mathematics materials. Computational thinking skills and mathematical disposition are two important aspects of mathematics education that are interrelated and influence each other.Keywords: computational thinking ability, mathematical disposition, mathematics learning